Right atrial strain in atrial fibrillation: the hidden side of the moon - Ruscio, Eleonora; Gabrielli, Francesca Augusta; Pinnacchio, Gaetano; Spera, Francesco Raffaele; Giordano, Federica; Scacciavillani, Roberto; Narducci, Maria Lucia; Bencardino, Gianluigi; Perna, Francesco; Crea, Filippo; Pelargonio, Gemma (Frontiers in Cardiovascular Medicine, 2025)
IntroductionLeft atrial (LA) remodeling in atrial fibrillation (AF) is well studied, whereas right atrial (RA) alterations remain poorly characterized. This study evaluates bi-atrial strain dynamics in patients with AF undergoing catheter ablation (CA).MethodsA total of 56 consecutive patients undergoing AF ablation were prospectively evaluated using speckle-tracking echocardiography and electrophysiological study before and after CA (median follow-up: 7 ± 3 months). A control group of 32 individuals undergoing CA for paroxysmal atrioventricular nodal reentrant tachycardia, without structural heart disease, was included for comparison.ResultsCompared to controls, AF patients exhibited significantly lower RA strain parameters (right atrial peak strain, reservoir phase, pRASr: 22.1 ± 12.6% vs. 29.8 ± 12.7%, p = 0.009) and greater RA mechanical dispersion (defined as the standard deviation of the time-to-peak positive strain, from the three RA segments, corrected for R-R interval, SD-regional-RA-TTP-N: 0.048 ± 0.015 vs. 0.038 ± 0.009, p = 0.020). Patients with persistent AF demonstrated a more pronounced RA dysfunction than those with paroxysmal AF (pRASr: 15.9 ± 11.7% vs. 24.8 ± 12.1%, p = 0.017; SD-regional-RA-TTP-N: 0.062 ± 0.030 vs. 0.043 ± 0.023, p = 0.016), despite comparable LA strain values. RA function correlated with both LA strain and volume parameters, and with the extent of abnormal LA electroanatomical substrate (pRASr and left atrial peak strain, reservoir phase, pLASr: r = 0.594, p < 0.001; pRASr and low-voltage LA area: r = −0.316, p = 0.018). Notably, RA parameters, rather than LA indices, were significantly reduced in patients with post-ablation AF recurrence (pRASr: 14.1 ± 11.7% vs. 24.6 ± 13.5%, p = 0.039; SD-regional-RA-TTP-N: 0.054 ± 0.031 vs. 0.032 ± 0.010, p = 0.002). However, the CHA2DS2-VASc score remained the sole independent predictor of AF recurrence (HR 1.47, 95% CI 1.003–2.158, p = 0.048).ConclusionRA function, assessed through strain imaging, was progressively impaired in more severe AF subtypes, strongly correlating with bi-atrial mechanical and electroanatomical properties. Furthermore, RA function was associated with AF recurrence after catheter ablation, highlighting its potential prognostic value.